Management of women with pregnancy-related pelvic girdle pain: an international Delphi study. (June 2022) - Aldabe, Daniela; Lawrenson, Peter; Sullivan, John; Hyland, Gail; Bussey, Melanie D.; Hammer, Niels; Bryant, Katrina; Woodley, Stephanie J.
Abstract: Objectives: Pregnancy-related pelvic girdle pain (PPGP) contributes to significant prenatal and postpartum impairments; however, various clinical practices exist around the conservative treatment of this condition. This study sought to reach a consensus on the essential components of PPGP management through an international Delphi survey of experts in women's health. Design and participants: Eighty-seven international experts in the field of PPGP were invited to participate and surveyed over three rounds. Round 1 of the survey utilised open-ended questions to gain feedback on 16 components of PPGP management previously identified by a focus group. Feedback from panel members guided modification and refinement of questions for Rounds 2 and 3. A 5-point Likert scale was used to rate level of agreement, with a minimum threshold for consensus of ≥75% agreement set across all survey rounds. Results: Forty-four of the 87 (50%) invited professionals agreed to participate in the panel, with 77% (34/44) of panellists contributing to all three rounds. Of the 16 initial components, 15 were included in Round 2. The final consensus was reached on 10 important components of assessment and management after Round 3: pain education, postural and ergonomic advice, social and lifestyle factors, psychological factors, cultural considerations, strengthening exercise, other exercise, exercise precautions, manual therapy and the use of crutches. Conclusion: This study identified 10 key components that should be considered in the management of PPGP. In addition, these components provide a potential framework for future research around the conservative management of PPGP.